Avramović’s Contribution to the Transition to Market Economy in Yugoslavia - Uvalić, Milica (Panoeconomicus, 2022)
The paper is dedicated to Dragoslav Avramović, a unique personality who played a key role in a historically important period for Federal Republic (FR) of Yugoslavia. After the successful implementation of his macroeconomic stabilization program, Avramović wanted to implement other important economic reforms. In November 1995, he prepared the “Program II” that contained fifteen measures, one of which was the “Democratization of property relations”. Avramović formed a Working Group in April 1996 that was to prepare a privatization program for FR Yugoslavia. The program was soon ready, proposing obligatory, comprehensive and fast privatization of all enterprises in FR Yugoslavia, using a combination of different methods. However, Avramović’s privatization program was not even officially discussed, since in mid-May 1995 he had to leave his position of Governor of the National Bank. The paper also points to the profound ideological differences among intellectuals at that time and to the wider consequences of Avramović’s departure.Keywords: Transition, Privatization, Property rights, Social property, Yugoslavia, Serbia. JEL: L33, P26, P31, P50.